La dependencia económica externa de Cuba y su repercusión sobre su política exterior - Mesa-Lago, Carmelo (Estudios Internacionales, 1982)
One of the most controversial aspects of the Cuban Revolution is to know if the previous economic and political dependence of the island with respect to the United States has not been replaced by a similar subordination relation with respect to the Soviet Union. This monograph attempts to clarify this controversy through an analysis of Cuba’s international economic and political relations. The first part examines the collection of economic data accumulated for the period 1959-1978 in order to determine the degree of economic dependence of Cuba with respect to the Soviet Union. In the second, which is surely more complex and subjective, an attempt is made to evaluate the influence that any economic dependency can have on Cuba’s foreign policy.